Treatment of Lennox-Gastaut syndrome: overview and recent findings - Kenou van Rijckevorsel (Dove Medical Press, 2008)
Kenou van RijckevorselReference Centre of Refractory Epilepsy, Cliniques Universitaires St Luc, Université Catholique de Louvain, Brussels, BelgiumAbstract: Lennox-Gastaut syndrome (LGS) is a rare, age-related syndrome, characterized by multiple seizure types, a specific electro-encephalographic pattern, and mental regression. However, published data on the etiology, evolution, and therapeutic approach of LGS are contradictory, partly because the precise definition of LGS used in the literature varies. In the most recent classification, LGS belongs to the epileptic encephalopathies and is highly refractory to all antiepileptic drugs. Numerous treatments, medical and non-medical, have been proposed and results mostly from open studies or case series have been published. Sometimes, patients with LGS are included in a more global group of patients with refractory epilepsy. Only 6 randomized double-blind controlled trials of medical treatments, which included patients with LGS, have been published. Overall, treatment is rarely effective and the final prognosis remains poor in spite of new therapeutic strategies. Co-morbidities need specific treatment. This paper summarizes the definition, diagnosis and therapeutic approach to LGS, including not only recognized antiepileptic drugs, but also “off label” medications, immune therapy, diet, surgery and some perspectives for the future.Keywords: Lennox-Gastaut syndrome, treatment, VNS, surgery, epileptic encephalopathies, LGS, refractory